Ageing of natural rubber vulcanizates in acid and alkali solutions - Varkey J K; Mathew N M; Pillai P V (Indian Journal of Natural Rubber Research, 1992)
Resistance of natural rubber vulcanizates towards hot aqueous solutions of a few industrially important chemicals was studied. Absorption of water by rubbers containing lyophilic materials is a diffusion/osmotic phenomenon. Retention of strength after ageing in distilled water is lower, compared to that after ageing in aqueous media containing acid or alkali, provided the media are inert towards rubber. As the concentration of acid or alkali in the ageing media increases, the tendency for water to diffuse into the rubber matrix gets reduced. Reinforcing and nonhydrophilic fillers were found to reduce water absorption.
Keywords: Ageing; Ageing; Chemical resistance; Chemical resistance; Natural rubber; Natural rubber; Vulcanizates; Vulcanizates; Water absorption; Water absorption